Les facteurs d'influence de la participation verbale en classe des étudiants universitaires : une revue de la littérature - Anastassis Kozanitis; Roch Chouinard (Revue Internationale de Pédagogie de l’Enseignement Supérieur)
The authors carried out a review of the literature on factors which influence undergraduates’ in class verbal participation. Several factors were identified and classified in three categories: those focusing on student characteristics, those related to teacher’s behavior, and those relevant to the learning environment. This categorization is an original contribution proposed by the authors in order to structure the body of knowledge.